SARM suppresses TRIF, TRAF3, and IRF3/7 mediated antiviral signaling in large yellow croaker Larimichthys crocea - Zhang, Jia Xi; Li, Ying; Tang, Jun Chun; Li, Kai Qing; Shen, Juan Juan; Liu, Chang; Jiang, Yong Hua; Zhang, Zi Ping; Wang, Yi Lei; Zou, Peng Fei (Frontiers in Immunology, 2023)
As a TIR domain-containing molecular, sterile α-and armadillo motif-containing protein (SARM) acts as an adaptor in Toll-like receptor (TLR) signaling, and also plays important roles in mediating apoptosis and neuronal injury. In the present study, the ortholog of SARM, named as Lc-SARM, was cloned and identified in large yellow croaker (Larimichthys crocea). The full-length ORF of Lc-SARM consists of 2,154 bp, encoding a protein of 717 amino acids (aa), which is comprised of an N-terminal ARM domain, two SAM domains, and a C-terminal TIR domain. Confocal microscopy revealed that Lc-SARM was mainly distributed in the cytoplasm, and the mRNA expression level of Lc-SARM was broadly distributed in all the detected organs/tissues, with the highest expression level found in the brain. The expression patterns of Lc-SARM could be induced in response to poly I:C, LPS, PGN stimulations, and Pseudomonas plecoglossicida infection. Notably, although the overexpression of Lc-SARM could significantly induce NF-κB, IRF3, IRF7, and type I IFN promoter activation, whereas the co-expression of Lc-SARM with Lc-TRIF, Lc-TRAF3, Lc-IRF3, or Lc-IRF7 significantly down-regulated the induction of NF-κB, IRF3, IRF7, or type I IFN promoter activation, and suppressed the antiviral effects as well as the downstream antiviral-related genes expression compared to the only overexpression of Lc-TRIF, Lc-TRAF3, Lc-IRF3, or Lc-IRF7. Co-immunoprecipitation (Co-IP) assays also demonstrated that Lc-SARM interacts separately with Lc-TRIF, Lc-TRAF3, Lc-IRF3, and Lc-IRF7. It is thus collectively suggested that Lc-SARM functions as a negative regulator in Lc-TRIF, Lc-TRAF3, and Lc-IRF3/7 involved antiviral signaling.